2011
DOI: 10.1016/s1995-7645(11)60197-1
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of silver nanoparticles by using mangrove plant extract and their potential mosquito larvicidal property

Abstract: The biosynthesis of silver nanoparticles with leaf aqueous extract of R. mucronata provides potential source for the larvicidal activity against mosquito borne diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(77 citation statements)
references
References 23 publications
5
69
1
2
Order By: Relevance
“…The efficacy of larvicidal activity of this plant was reported at 118.2 ppm (Lc 50 ) and 227 ppm (Lc 90 ) by Raut et al (2010) [26] [27]. However in our study we found that Lc 90 was recorded at 100 ppm in solvent (ethanol) extraction and the AgNPs of P. pinnata has shown the significantly lower concentration in comparison to earlier publications of their Table 2.…”
Section: Discussioncontrasting
confidence: 76%
“…The efficacy of larvicidal activity of this plant was reported at 118.2 ppm (Lc 50 ) and 227 ppm (Lc 90 ) by Raut et al (2010) [26] [27]. However in our study we found that Lc 90 was recorded at 100 ppm in solvent (ethanol) extraction and the AgNPs of P. pinnata has shown the significantly lower concentration in comparison to earlier publications of their Table 2.…”
Section: Discussioncontrasting
confidence: 76%
“…The AgNps (AgNps) synthesised using leaf extract of Rhizophora mucronata have excellent larvicidal activity (LC 50 and LC 90 ) against the larvae of Aedes aegypti and Culex quinquefasciatus with respect to 0.585 mg/L and 2.615 mg/L and 0.891 and 6.291 mg/mL (Gnanadesigan et al, 2011 . AgNps from bark aqueous extract of Ficus racemosa have shown excellent larvicidal activity against C. quinquefasciatus (LC 50 =67.72 and 63.70 mg/L) and C. gelidus (LC 50 =12.00 and 11.21 mg/L) (Velayutham et al, 2012).…”
Section: Antiparasitic Studymentioning
confidence: 99%
“…A vector of Wuchereria species called Culex quinquefasciatus was responsible for causing lymphatic Filariasis which are wide spread in the tropical region with 120 million people infected and 40 million people are under clinical manifestation (Veerakumar et al, 2013). Two million malarial cases were reported annually in India (Gnanadesigan et al, 2011). Due to the development of insecticides resistance, biological magnification, serious effect on environmental quality and destruction of nontarget organism, the vector controlling methods involving chemical insecticides are becoming less effective (Suganya et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…aegypti showed very sensitivity towards the mortality with biogenic silver nanoparticles (Table 3). [66][67][68][69][76][77][78][79][80][81][82] Besides these actions, silver nanoparticles were effective against Anopheles and Culex. [83][84][85] Against Ae.…”
Section: Nanoinsecticide Against Mosquitoesmentioning
confidence: 99%